1998
DOI: 10.2151/jmsj1965.76.3_453
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Equatorial QBO on the Northern Hemisphere Winter Circulation of a GCM

Abstract: The influence of a simulated equatorial quasi-biennial oscillation (QBO) on the Northern Hemisphere winter was studied by analyzing output data from a general circulation model (GCM). The differences between the 7-50hPa equatorial QBO phases of the January-March (JFM) averaged zonal wind composite exhibit a weaker polar-night jet during the easterly phase of the equatorial QBO and a stronger polar-night jet in the westerly phase. The Eliassen-Palm flux of planetary waves is stronger and more convergent in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…2a) during the first winter occurs during the October-November-December months, rather than December-January-February months. Also, it has to be noted that here we try to simulate one event rather than calculate the composites of several cases as is carried out in the previous modeling/observational studies (Holton and Tan, 1980;Niwano and Takahashi, 1998;Calvo et al, 2007). Hence, the vortex is highly sensitive to the winter months selected and the dynamics of the vortex is non-linear.…”
Section: Hpa Geopotential Height Response In Boreal Wintermentioning
confidence: 99%
See 1 more Smart Citation
“…2a) during the first winter occurs during the October-November-December months, rather than December-January-February months. Also, it has to be noted that here we try to simulate one event rather than calculate the composites of several cases as is carried out in the previous modeling/observational studies (Holton and Tan, 1980;Niwano and Takahashi, 1998;Calvo et al, 2007). Hence, the vortex is highly sensitive to the winter months selected and the dynamics of the vortex is non-linear.…”
Section: Hpa Geopotential Height Response In Boreal Wintermentioning
confidence: 99%
“…Hamilton (1998) reproduced the Holton-Tan effect making use of a general circulation model run for a continuous 48-year period with a time varying tropical momentum forcing that produced a 27-month QBO in the equatorial zonal wind with realistic QBO features. Niwano and Takahashi (1998) investigated this feature using their model that spontaneously produces a QBO-like oscillation in the tropics with a period of about 1.4 years and revealed that the NH polar vortex was weaker in the easterly QBO phase based on the January-March composites of the equatorial wind averaged between 7 and 50 hPa. Calvo et al (2007) using the middle atmosphere version of ECHAM5, which has an internally generated QBO pointed out a significantly warm polar vortex in the easterly QBO phase in January-February months and a cold, strong polar vortex in the westerly QBO phase in the December-January months.…”
Section: Introductionmentioning
confidence: 99%
“…Niwano and Takahashi (1998) investigated the influence of the equatorial QBO that was simulated in their GCM on the NH winter circulation, while Hamilton (1998) investigated the effects of an imposed QBO using the GFDL SKIHI GCM. Both studies confirmed the Holton-Tan relationship and showed modest effects of the QBO to the winter troposphere.…”
Section: Troposphere-stratosphere Coupled Variationmentioning
confidence: 99%
“…They suggested that sudden stratospheric warmings are less likely during QBO W, when the zero wind line lies in the summer subtropics. The QBO modulates the position of critical surfaces and thus the propagation and absorption of extratropical planetary Rossby waves (e.g., Holton and Austin 1991;Haynes et al 1991;O'Sullivan and Young 1992;O'Sullivan and Chen 1996;Kinnersley and Pawson 1996;Hamilton 1998;Niwano and Takahashi 1998;Gray et al 2001). When QBO easterlies (E) are in the tropical stratosphere, the zero wind line lies in the winter subtropics, and planetary Rossby wave breaking (RWB) is more likely to occur in the northern winter (McIntyre and Palmer 1983).…”
Section: Introductionmentioning
confidence: 99%